SAT0371 Hla-B27 Status Is Associated with tnfα Inhibitor Treatment Outcomes in Ankylosing Spondylitis and Non-Radiographic Axial Spondyloarthritis – Observational Cohort Study from The Nationwide Danbio Registry. (15th July 2016) - Glintborg, B.; Juul Sørensen, I.; Østergaard, M.; Mahamoud, A.A.; Krogh, N.S.; Andersen, L.S.; Raun, J.L.; Hendricks, O.; Kowalski, M.R.; Danielsen, L.; Christensen, S.R.; al Chaer, N.; et al.
Abstract : Background: Little is known about tumor-necrosis-factor-alpha-inhibitor (TNFi) treatment outcomes in Ankylosing Spondylitis (AS) vs. non-radiographic axial spondyloartrhitis (nr-axSpA). Objectives: To compare baseline disease activity and treatment outcomes in biologic naïve patients with AS and nr-axSpA, who initiate TNFi treatment in clinical practice taking potential confounders into consideration. Methods: We performed an observational cohort study based on prospectively registered data in the nationwide Danish quality registry, DANBIO, including baseline and 3–6 months' follow-up markers of disease activity (visual analogue score (VAS) global disease, Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), BAS metrology index (BASMI) and serum C-reactive protein (CRP)). Treatment response was defined as either a 50% or a 20 mm reduction in BASDAI after 3–6 mths treatment. We used Kaplan-Meier plots, Cox and logistic regression analyses to study the impact of diagnosis (AS vs. nr-axSpA) and potential confounders (gender, age, start year, HLA-B27, disease duration, TNFi type, smoking, baseline disease activity) on TNFi adherence and response. Numbers are medians (IQR) unless otherwise stated. Results: We identified 1, 250 TNFi naïve patients in DANBIO with axSpA according to the treating physician. Of these, 50% had AS, 28% nr-axSpA and 21% lacked X-rays of sacroiliac joints. Baseline demographics and disease activity differed in nr-axSpA vs. AS (Table ). Response rates were similar, but treatment adherence was poorer in nr-axSpA than in AS (univariate, Table ). In confounder adjusted analyses, axSpA sub-diagnosis was not associated with response rates or treatment adherence. However, HLA-B27 positivity was associated with better treatment adherence (HLA-B27 neg/pos, nr-axSpA: HR 1.74 (1.29–2.36), AS: HR 2.04 (1.53–2.71.), both p<0.0001) (Figure ) and higher response rates (nr-axSpA: 30%/55%, AS: 29%/54%, univariate, both p<0.05). Similar results for HLA-B27 were found in confounder-adjusted analyses. Conclusions: In this nationwide cohort, patients with nr-axSpA had higher subjective disease activity at the start of the first TNFi treatment but had similar confounder adjusted treatment adherences and response as AS pts. HLA-B27 positive pts had better outcomes irrespective of axSpA sub-diagnosis. Disclosure of Interest: B. Glintborg: None declared, I. Juul Sørensen: None declared, M. Østergaard: None declared, A. A. Mahamoud: None declared, N. S. Krogh: None declared, L. Andersen: None declared, J. Raun: None declared, O. Hendricks: None declared, M. Kowalski: None declared, L. Danielsen: None declared, S. Christensen: None declared, N. al Chaer: None declared, R. Pelck: None declared, H. Nordin: None declared, J. Pedersen: None declared, D. Kraus: None declared, I. Jensen Hansen: None declared, J. Espesen: None declared, A. Schlemmer: None declared, A. Loft Speakers bureau: MSD, L. Salomonsen: None declared, L. Dreyer: None declared, M. Hetland: None declared